Use of Big Book Learning Media to Improve Students’ Beginning Reading Skills in Primary Schools - Nurani, Riga Zahara; Mahendra, Hatma Heris (Mimbar Sekolah Dasar, 2019)
This study is motivated by the fact that there are still many lower grade students who have not been able to read fluently. Big book learning media can be used by teachers to teach beginning reading to lower grade students. The purpose of this study is to describe the use of big book learning media to improve beginning reading skills. The study employed a qualitative descriptive method. The subjects were second-grade primary school students who were still unable to read. The research was conducted in one of the primary schools in Tasikmalaya City. The results revealed that students were more enthusiastic in learning to read using big book learning media, which could be seen from an increase in students' reading skills in each meeting. By using big book learning media, in addition to learning to read through a series of letters, students were able to learn to read through images followed by the writing. Therefore, big book learning media can be used to improve students' reading skills.